Developing a model to reduce blindness in India: The international centre for advancement of rural eye care - Dandona Lalit; Dandona Rakhi; Shamanna B; Naduvilath Thomas; Rao Gullapalli (Indian Journal of Ophthalmology, 1998)
With the continuing high magnitude of blindness in India, fresh approaches are needed to effectively deal with this burden on society. The International Centre for Advancement of Rural Eye Care (ICARE) has been established at the L.V. Prasad Eye Institute in Hyderabad to develop such an approach. This paper describes how ICARE functions to meet its objective. The three major functions of ICARE are design and implementation of rural eye-care centres, human resource development for eye care, and community eye-health planning. ICARE works with existing eye-care centres, as well as those being planned, in underserved areas of India and other parts of the developing world. The approach being developed by ICARE, along with its partners, to reduce blindness is that of comprehensive eye care with due emphasis on preventive, curative and rehabilitative aspects. This approach involves the community in which blindness is sought to be reduced by understanding how the people perceive eye health and the barriers to eye care, thereby enabling development of strategies to prevent blindness. Emphasis is placed on providing good-quality eye care with attention to reasonable infrastructure and equipment, developing a resource of adequately trained eye-care professionals of all cadres, developing a professional environment satisfactory for patients as well as eye-care providers, and the concept of good management and financial self-sustainability. Community-based rehabilitation of those with incurable blindness is also part of this approach. ICARE plans to work intensively with its partners and develop these concepts further, thereby effectively bringing into practice the concept of comprehensive eye care for the community in underserved parts of India, and later in other parts of the developing world. In addition, ICARE is involved in assessing the current situation regarding the various aspects of blindness through well-designed epidemiologic studies, and projecting the eye-care needs for the future with the help of reliable information. With balanced attention to infrastructure, manpower, financial self-sustenance, and future planning, ICARE intends to develop a practical model to effectively reduce blindness in India on a long-term basis.